Employers' recruitment of disadvantaged groups: exploring the effect of active labour market programme agencies as labour market intermediaries. (21st November 2017) - Ingold, Jo; Valizade, Danat
Abstract: This article draws on an original comparative survey of employers in the UK and Denmark to analyse the role of active labour market programmes (ALMPs) in employers' recruitment of disadvantaged groups. Using the framework of Bonet et al. to conceptualise agencies delivering ALMPs as labour market intermediaries (LMIs), the effect of ALMPs on employers' recruitment was tested against organisational factors involving firm size and selection criteria. Although ALMPs marginally increased employers' probability of recruiting the long‐term unemployed in both countries and lone parents in Denmark, their effect was negligible compared with firm size and employers' selection criteria. While ALMP agencies have the potential to increase employers' recruitment of disadvantaged groups, this is constrained when they act as basic 'information provider' LMIs. ALMP agencies' inability to act effectively as 'matchmaker' LMIs leads to a failure to overcome rigid intra‐organisational barriers to such recruitment.